Improvement of the Caenorhabditis elegans growth and reproduction test to assess the ecotoxicity of soils and complex matrices. (17th July 2013) - Huguier, Pierre; Manier, Nicolas; Méline, Camille; Bauda, Pascale; Pandard, Pascal
Abstract: A growth and reproduction test using the nematode Caenorhabditis elegans was recently standardized by the International Organization for Standardization (ISO). Performing the ISO 10872 protocol (2010) revealed some drawbacks when applied to soil or soil mixed with complex matrices. The authors propose some modifications to the current protocol to normalize the test conditions. An appropriate range of moisture conditions was determined as a percentage of the water‐holding capacity (WHC) of the soil. According to the authors' results, C. elegans tests can be performed in the range of 60% to 100% WHC. To ensure that the modifications of the protocol did not affect the organisms' recovery, extraction ratios for the juveniles were subsequently estimated. The modified protocol was found to be as reliable as the standard one concerning recovery of juveniles (over 80%). The protocol was also applied to several chemicals to investigate their potential as reference chemicals for soil toxicity tests. Boric acid, copper chloride, and nickel sulfate showed deleterious effects in a concentration‐dependent manner for the growth and reproduction of C. elegans . Finally, the modified protocol was used to assess the growth and reproduction of C. elegans in soil amended with a limed sewage sludge. The authors conclude that the C. elegans modified protocol is a promising tool for the assessment of soil toxicity as well as the toxicity of mixtures with complex matrices. Environ Toxicol Chem 2013;32:2100–2108. © 2013 SETAC